IMPLEMENTASI CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KOMPETENSI SISWA SMK PADA PAKET KEAHLIAN TEKNIK SEPEDA MOTOR - Agusfianto, Bambang (2014)
The problem of this research was still low motivation due to the impact of teachers still use the methods in the class lectures and demonstrations and workshops without involving the environmental conditions around the students and the high failure rate of attainment of competency to more than 50% of the subjects improved automatic transmission system. This study was conducted at SMK 1 Simpangkatis Central Bangka Regency of Bangka Belitung Islands. The method of the study was used the quasi-experimental design with nonequivalent control group design using a pretest and posttest results. The instrument was used a written test instruments, test performance, questionnaire responses of student learning and teaching observation sheet. The Improvement results of the written test in the experimental class obtained from the average pretest score of 43.3 increased by an average of 81.8 posttest written test so that the difference in improvement (gain) difference of 38.5 and a normal increase in the written test result (n-gain ) sebesat 67.9. The Improvement results of the written test in the experimental class obtained from the average value increased by 42.9 average pretest-posttest average of 69.5 so that the increasing in the written test (gain) difference of 26.6 and a normal increase in the written test result (n-gain ) sebesat 46.6. The comparison of the average test performance score in the experimental class obtained at 87.9 while value of the control class average was 76.9. The differences between the result performance test the two classes is 11.0. The conclusion that the differences from increasing the competence automatic transmission system improvements the motorcycle technical expertise package that uses contextual teaching and learning approach was better than that using the conventional approach. In general, the students gave positive responses to the learning contextual teaching and learning and student competency differences seen from the results of the written test and performance test.